MON-272 Clinical Relevance of Serum Prolactin Levels to Inflammatory Reaction in Male Patients - Yamamoto, Koichiro (J Endocr Soc, 2020)
PRL is a polypeptide hormone that is, in phylogeny, well conserved but elicits various species-dependent functions. PRL is related to the regulation of osmotic pressure in fish and amphibians, fat retention in reptiles and birds, and glucose-lipid metabolism, bone homeostasis and development of the mammary gland in mammals. In humans, PRL secretion is regulated in an inhibitory manner by dopaminergic neurons that project from the hypothalamus to PRL-producing cells in the anterior pituitary gland. Since dopaminergic actions are mainly mediated by D2R, various agents that bind D2R can affect serum PRL levels. In the clinical aspect, hyperprolactinemia is considered in cases with galactorrhea, infertility and sexual dysfunction. Other causes of hyperprolactinemia include hypothyroidism, chronic kidney disease and pregnancy. Also, PRL receptors have been considered as therapeutic targets for some cancers and autoimmune diseases. Given that several pathophysiological functions related to PRL have been recently uncovered, the utility of measuring serum PRL levels could be more widely applicable for a clinical setting. We therefore attempted to reveal the relevance of PRL levels to various clinical parameters in patients who visited a general medicine department. We reviewed medical records of 353 patients whose serum PRL levels were measured in our department during the period from 2016 to 2018. Patients lacking detailed clinical records (n=194) and patients taking medications that affect D2R (n=19) were excluded from this study. Data were analyzed for 140 patients (42 males, aged 49 ± 18 years; 98 females, 45 ± 19 years) in whom various pain and general fatigue were major symptoms at the first visit and in whom hypertension and dyslipidemia were frequently seen in past histories. Average PRL levels were significantly lower in males than in females. The median PRL level in males was 6.5 ng/ml (IQR: 4.2–10.3) ng/ml and that in females was 8.1 ng/ml (5.9–12.9). Patients were divided into two groups depending on whether PRL levels were higher than 10 ng/ml. The group of males with relatively high PRL levels (≥10 ng/ml) had significantly lower levels of serum albumin and higher levels of serum LDH. Of note, there were significant correlations of male PRL levels to erythrocyte sedimentation rate (ESR) (r=0.6), serum LDH (r=0.4) and albumin level (r=-0.5), and TSH/FT4 ratio (r=0.5). On the other hand, female PRL levels were negatively correlated to age (r=-0.2) and serum levels of FSH (r=-0.3) and positively correlated to serum levels of GH (r=0.3). Collectively, the results revealed that PRL levels had gender-specific relevance to various clinical factors. It is notable that PRL levels in males were related to inflammatory status shown by high ESR and low serum albumin and were also associated with a hypothyroid condition.